The Effect of Papaya (Carica Papaya L.) Leaves on Adolescents with Dysmenorrhea - Rahmah, Desy Aulia; Priastomo, Mukti; Rijai, Laode (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2020)
Papaya leaves (Carica papaya L.) contain active compounds of flavonoids and alkaloids which have the function of reducing dysmenorrhea. Dysmenorrhea is a condition that occurs at any time during menstruation that experiences pain or pain in the abdominal and pelvic area so it can interfere with activities and require treatment. This study aims to determine the effect of the effectiveness of offering papaya leaf herbal drink in reducing dysmenorrhea. The research design used in this study was a pre-experimental research design with a pre-experimental test design with accidental sampling technique. Measurement of pain intensity using pain scale measurements (Pre-Test) and final pain (Post-test using a numerical rating scale, time of incidence on the first and second day of menstruation (77%), location of lower abdominal dysmenorrhea (92%), symptoms of dysmenorrhea, namely abdominal pain (75%), moderate pain scale (48%)], and treatment was resting (63%). Based on the results of the study, subjects who were given a papaya leaf herbal drink were able to reduce the pain scale of dysmenorrhea with a large difference in pain scale reduction in the treatment group of chopped papaya leaf stew by 3,2.